Statistics for Management and Economics - Warrack, Keller (United States of America Brooks/Cole-Wadsworth, 2000)
This edition of Statistics for Management and Economics integrates statistics into business and economics curricula. We continue to emphasize real examples, exercises and cases, and the use of computers and software including Microsoft Excel.
Donated by: Surajeet Chakravarty
Keywords: Statistics; Economics